Phantoms ultrassônicos mimetizadores de estágios da consolidação óssea - Miguel, Fernanda Catelani (2018)
Quantitative Ultrasound is a non-invasive, non-ionizing, easy-to-use technique applied in studies on the propagation of ultrasound in tissues, but these studies do not address the use of ultrasonic phantoms that mimic the stages of bone healing. Thus, the objective of this study is to develop ultrasonic phantoms of three stages of bone consolidation, using automotive windshield glass as an original raw material. Ten phantoms were produced at each of the four sintering temperatures (625, 645, 657 and 663 °C) and the following parameters were evaluated: ultrasonic longitudinal phase velocity (CPH), coefficients of apparent (αPH) and corrected (αC) ultrasound attenuation and bulk density (DPH). The acoustic properties were evaluated in three regions of the phantoms (R1, R2 and R3) and DPH was obtained by the Archimedes principle. It was observed that the CPH, αPH, αC and DPH parameters are compatible with that of the compact bone and that CPH values of the 663 (4,406 ± 210 m∙s-1 ), 625 (2,398 ± 331 m∙s-1 ), 657 (3,529 ± 124 m∙s-1 ) and 645 ºC (3,974 ± 141 m∙s-1 ) temperatures are similar, respectively, to the intact bone, soft callus, stiff callus and ossified tissue; moreover, αC values could be classified as the initial (625 and 657 ºC) and final (645 and 663 ºC) stages of healing bone, corresponding to values of 8 ± 3.9 to 10 ± 2.2 dB∙cm-1 and from 3 ± 0.8 to 4 ± 0.5 dB∙cm-1 , respectively. The phantoms could be used in diagnostic and therapeutic studies using ultrasound.